Stress Urinary Incontinence: An Unsolved Clinical Challenge - Niklas Harland; Simon Walz; Daniel Eberli; Florian A. Schmid; Wilhelm K. Aicher; Arnulf Stenzl; Bastian Amend (Biomedicines, 2023)
Stress urinary incontinence is still a frequent problem for women and men, which leads to pronounced impairment of the quality of life and withdrawal from the social environment. Modern diagnostics and therapy improved the situation for individuals affected. But there are still limits, including the correct diagnosis of incontinence and its pathophysiology, as well as the therapeutic algorithms. In most cases, patients are treated with a first-line regimen of drugs, possibly in combination with specific exercises and electrophysiological stimulation. When conservative options are exhausted, minimally invasive surgical therapies are indicated. However, standard surgeries, especially the application of implants, do not pursue any causal therapy. Non-absorbable meshes and ligaments have fallen into disrepute due to complications. In numerous countries, classic techniques such as colposuspension have been revived to avoid implants. Except for tapes in the treatment of stress urinary incontinence in women, the literature on randomized controlled studies is insufficient. This review provides an update on pharmacological and surgical treatment options for stress urinary incontinence; it highlights limitations and formulates wishes for the future from a clinical perspective.